The Effect of Applying Internal Auditing Standards on The Effectiveness of Internal Control In Service Units: Iraq Case Study - Ibrahim Naeem Hasan; Raed Naeem Rashed (Utan Kayu Publishing, 2024)
Internal auditing is one of the functions that characterize the economic unit, as some researchers indicated that one year of internal auditing is equivalent to the work of three years of external auditing, Internal audit is an independent evaluation body located within the organizational structure of the economic unit and is considered one of the means of internal control. The researcher recommends the need to give the internal audit function in government institutions and sufficient attention as the basic function that can provide assurance services (financial audit, performance audit or operational audit, rapid response) and advisory services (evaluation services, facilitation services, treatment services) as well as its importance in Improving and strengthening guidance for service institutions.